Designing a ’modern’ abacus for early childhood mathematics - Skoumpourdi, Chrysanthi (Teaching Mathematics and Computer Science, 2009)
In this paper, the design of a multi-material, the ’modern’ abacus (’modabacus’), for developing early childhood mathematics, is proposed. Presenting the main theories for the design of educational materials as well as similar materials and their educational use, it appears that a new material is needed. The ’modabacus’ would be an apparatus which could serve as a multi-material for acting out mathematical tasks as well as a material that could hopefully overcome the limits and restrictions of traditional abacuses and counting boards.